PENGARUH BERBAGAI EKSTRAK AKAR DALAM STIMULASI INFEKSI CENDAWAN MIKORIZA ARBUSKULA (CMA) PADA Tithonia diversifolia - Agustian Agustian; Arwie Delfi; Lusi Maira (Jurnal Solum, 2012)
In the first stage of arbuscular-mycorrhiza (AMF) fungi development on plant roots showed that root exudates, is a substance that determines the success of the establishment of mycorrhizal symbiosis. This secondary metabolites produced is intended to keep mold growth during the phase preinfection. Therefore, it is interesting to know whether to add the root extract of the plant could enhance CMA fungal infection in its host plant. The purpose of this study was to determine the type of root extract can stimulate CMA infection at the root and its influence on the growth of Tithonia diversifolia. This experiment used Completely Randomized Design (CRD) with 4 treatments and 3 replications, and continued with advanced test DNMRT at level 5%. The treatments assayed were: control, Tris-HCl buffer pH 7 (A), root extract of weed Imperata cylindrica (B); root extract of taro (C), and root extract of cassava (D). Base on the results obtained we concluded that the extract of the roots of weeds, taro and cassava does not give effect to the increased growth of Tithonia. However, the roots extract stimulated and had influenced on the percentage and intensity of AMF infection at the root of Tithonia and the number of spores obtained in the rhizosphere of Tithonia. In this case the root extract of taro showed the best stimulatory effect of infection with the percentage and intensity of infection are 99.3% and 30.59% consecutively with the number of spores found reach 113 spores/ 100 g soil.Key words: Stimulation, arbuscular-mycorrhiza, root extract, Tithonia diversifolia